Intrafraction motion analysis in online adaptive radiotherapy for esophageal cancer - Mick R. Boekhoff; Jan J.W. Lagendijk; Astrid L.H.M.W. van Lier; Stella Mook; Gert J. Meijer (Physics and Imaging in Radiation Oncology, 2023)
Intrafraction motion during magnetic resonance (MR)-guided dose delivery of esophageal cancer tumors was retrospectively analyzed. Deformable image registration of cine-MR series resulted in gross tumor volume motion profiles in all directions, which were subsequently filtered to isolate respiratory and drift motion. A large variability in intrafraction motion patterns was observed between patients. Median 95% peak-to-peak motion was 7.7 (3.7 – 18.3) mm, 2.1 (0.7 – 5.7) mm and 2.4 (0.5 – 5.6) mm in cranio-caudal, left–right and anterior-posterior directions, relatively. Furthermore, intrafraction drift was generally modest (<5mm). A patient specific approach could lead to very small margins (<3mm) for most patients.